2016
DOI: 10.7554/elife.19484
|View full text |Cite
|
Sign up to set email alerts
|

Smad4 restricts differentiation to promote expansion of satellite cell derived progenitors during skeletal muscle regeneration

Abstract: Skeletal muscle regenerative potential declines with age, in part due to deficiencies in resident stem cells (satellite cells, SCs) and derived myogenic progenitors (MPs); however, the factors responsible for this decline remain obscure. TGFβ superfamily signaling is an inhibitor of myogenic differentiation, with elevated activity in aged skeletal muscle. Surprisingly, we find reduced expression of Smad4, the downstream cofactor for canonical TGFβ superfamily signaling, and the target Id1 in aged SCs and MPs d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 47 publications
2
48
0
1
Order By: Relevance
“…IGF-1 affects the balance between protein synthesis and protein degradation thus inducing muscle hypertrophy, whereas TGFβ negatively controls muscle growth (Schiaffino et al, 2013). Interestingly, recent studies demonstrated a new role for the TGFβ/Smad pathway in satellite cell expansion (Paris et al, 2016) and differentiation . During the final steps of muscle remodelling the vasculature and innervation patterns are restored and new MuSCs are set aside.…”
Section: Cellular Regulators Of Muscle Repair and Their Regenerative mentioning
confidence: 99%
“…IGF-1 affects the balance between protein synthesis and protein degradation thus inducing muscle hypertrophy, whereas TGFβ negatively controls muscle growth (Schiaffino et al, 2013). Interestingly, recent studies demonstrated a new role for the TGFβ/Smad pathway in satellite cell expansion (Paris et al, 2016) and differentiation . During the final steps of muscle remodelling the vasculature and innervation patterns are restored and new MuSCs are set aside.…”
Section: Cellular Regulators Of Muscle Repair and Their Regenerative mentioning
confidence: 99%
“…To examine growth capacity, FACS‐purified SCs from castrated and sham muscles were plated at low density (30 cells per well) in a clonal growth assay. Cultures of 100 FACS‐purified SCs or less can identify a deficit in the clonal growth capacity of aged SCs [2,6,31]. We found no significant difference in clonal growth between SCs derived from sham or castrated skeletal muscles (Figure 2A, B).…”
Section: Resultsmentioning
confidence: 89%
“…The skin overlaying the tibialis anterior (TA) muscle was then carefully shaved. The TA was directly injected with a 1.2% solution of BaCl 2 in normal saline [2]. At 28 days post-injury, injured and contralateral (uninjured) TAs were collected.…”
Section: Skeletal Muscle Injury and Regenerationmentioning
confidence: 99%
See 2 more Smart Citations